Role of health sector in road traffic injuries prevention: A public health approach - Saber Azami-Aghdash (Wolters Kluwer Medknow Publications, 2021)
Background: Although the main burden of the Road Traffic Injuries (RTIs) is on the health sector, compared with other sectors, no clear definition is available about its role in the prevention of the RTIs. So this study has been performed to define the role of the health sector in the prevention of RTIs –before the incidence. Methods: In this qualitative study with a grounded theory approach, the possible roles of the health sector in the prevention of the RTIs were identified in three phases. At the first stage of the study, the roles of the health system in the prevention of the RTIs identified from the literature. In the next step, semi-structured interviews (ranged from 45 to 90 minutes) with 42 experts were done for identifyingroles. Finally, Consensus attained on the identified roles by using the Delphi technique and with the participation of 30 experts. Results: Literature review and interviews resulted in 42 and 86 roles for the health sector in the prevention of the RTIs, respectively. After removing the duplicates and merging the similar, 46 roles were entered into Delphi. Five roles excluded in the Delphi leaving 41 roles in 7 dimensions of communications (6 roles), intra-sector cooperation (9 roles), inter-sector leadership (6 roles), evaluation (6 roles), research (5 roles), education (3 roles), and health-specific issues (6 roles). Conclusions: It seems that the health sector can help an impressing reduction of the RTIs by playing the roles identified in this study, which the most important of them is Communication/Informing role. So first the general public and then the health sector itself would benefit from it.